Legal And Administrative Mechanisms To Combat Corruption - Cheddadi, Mohcen (جامعة الوادي - University of Eloued, 2023)
ملخص: تزايد الإهتمام بموضوع الفساد المالي والإداري في معظم دول العالم لما يترتب عن انتشاره من انعكاسات خطيرة تمس مختلف المجالات في الدولة، فضلا عن ما يشكله من تهديد خطير يمس أمن واستقرار المجتمع. إذا كانت الدول على اختلاف تقدمها وتطورها تعاني من انتشار ظاهرة الفساد الإداري والمالي ، إلا اننا نجد الدول المتخلفة أو النامية الأكثر تضررا من استفحاله، وذلك راجع لأسباب عدة على غرار تدني المستوى المعيشي للموظف العمومي في الدولة من جهة، وضعف المستوى الثقافي والوعي العام للمواطن عموما من جهة ثانية. وعليه فإن مكافحة للفساد المالي والإداري في مثل هذه ظروف تستلزم الجمع بين آليتين إثنتين إحداها وقائية تهدف إلى الحيلولة دون وقوعه وانتشاره، وأخرى عقابية تستهدف توقيع عقوبات وجزاءات على كل من يثبت ارتكابهم لجرائم الفساد.Abstract: Increased interest in the issue of financial and administrative corruption in most countries of the world due to the serious repercussions of its spread affecting various fields in the country, in addition to the serious threat it poses to the security and stability of society. If countries of different progress and development suffer from the spread of the phenomenon of administrative and financial corruption, however, we find the underdeveloped or developing countries most affected by its exacerbation, and this is due to several reasons such as the low standard of living of public servants in the state on the one hand, and the poor cultural level and general awareness of the citizen in general On the other hand. Accordingly, the fight against financial and administrative corruption in such circumstances requires the combination of two mechanisms, one of which is preventive, aimed at preventing its occurrence and spread, and another punitive, aimed at imposing penalties and penalties on all those found guilty of corruption crimes
مقال
Keywords: corruption ; Confronting ; Legal Mechanisms ; Administrative Mechanisms